Alcohol and tobacco variables in the assessment of internal validity in an unmatched case-control study of occupational cancer in the Campania Region of Italy, 1988-1990 - Jhangari, Gian S.; Soskolne, Colin L.; Pagano, Giovanni; Botte, Gerardo; Di Cintio, Patrizia (European Journal of Oncology and Environmental Health, 2017)
Aim. In order to explore whether cancer incidence in organs other than the larynx is associated with occupational exposure to strong inorganic acid mists, a study of 513 in-patients in the Campania Region of Italy was undertaken in the period 1988-1990. Patients and methods. All male in-patients, resident in Campania and aged 35-74 years at the time of diagnosis were eligible. Cases comprised confirmed incident diagnoses of cancers of the respiratory tract, and bladder cancer. Controls included patients with a diagnosis of other cancers, as well as non-neoplastic conditions, traumas and burns. Interviewer-administered questionnaires were used to solicit demographic information, lifestyle characteristics, and occupational histories. Retrospective exposure assessments resulted in 20 exposure-specific industrial hygienist classifications. Cigarette smoking was calculated as “cigarettepack-year-equivalents”, and alcohol consumption was calculated as “alcohol-gram-year-equivalents”. Cut points were set corresponding to “high”, “moderate”, “low”, and “very low/no” exposure on their respective frequency distributions. Results. Case-control comparisons rendered dose-response trends for tobacco and alcohol consumption. In addition, positive associations regarding occupational risk factors, controlled for age and tobacco consumption, also are consistent with the literature. Conclusions. This paper reports the underlying methods of the study and demonstrates the internal validity of our dataset. Well-established lifestyle and occupational cancer risk factors have been able to be replicated here. The specific results linking workplace acid exposure to both respiratory tract cancer and to bladder cancer, controlling for most established risk factors, are published as companion papers in the same issue of the Journal.